Strengthening Village Governance Based on Public Accountability in Realizing Good Governance - Hikmat (Inovasi Sosial : Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to analyze and formulate a model for strengthening village governance based on public accountability in realizing good governance. The main issues raised are the still low transparency, community participation, and accountability in financial management and public services at the village level, which has implications for low public trust in the village government. This study uses a qualitative approach with a case study design in several villages that serve as the research locus. Data were collected through in-depth interviews, participant observation, and analysis of village financial planning and reporting documents. Data analysis was conducted interactively through data reduction, data presentation, and drawing conclusions. The results show that strengthening village governance requires an integration between budget transparency, community participation in development planning, strengthening internal control systems, and optimizing the use of information technology in village public administration. In addition, the capacity of village officials in financial management and public services is a key factor in creating sustainable accountability. The resulting model emphasizes a collaborative approach between the village government, the Village Consultative Body, and the community through inclusive deliberation mechanisms and transparent financial reporting. The implications of this research provide conceptual contributions to the development of a public accountability-based village governance model as well as practical recommendations for local governments in strengthening village monitoring and development systems. Thus, strengthening public accountability-based governance becomes a strategic strategy in realizing the principles of good governance at the village government level.